2011
DOI: 10.1021/bi2001483
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Three Novel Hydroxamate-Based Zinc Chelating Inhibitors of the Clostridium botulinum Serotype A Neurotoxin Light Chain Metalloprotease Reveals a Compact Binding Site Resulting from 60/70 Loop Flexibility

Abstract: Neurotoxins synthesized by Clostridium botulinum bacteria (BoNT), the etiological agent of human botulism, are extremely toxic proteins making them high-risk agents for bioterrorism. Small molecule inhibitor development has been focused on the light chain zinc-dependent metalloprotease domain of the neurotoxin, an effort that has been hampered by its relatively flexible active site. Developed in concert with structure-activity relationship studies, the X-ray crystal structures of the complex of BoNT serotype A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…Although much smaller tetrapeptide inhibitors of LcA with nM k i have been described (30), the significance of the 32-mer peptide as an inhibitor lies in the fact that it is a part of the LcA itself, not resembling the true substrate. Recently, three hydroxamate-containing small molecule inhibitors having 5-6 M k i values were found to induce the most compact catalytic pocket in LcA (34).…”
Section: Inhibition Of Lca Activity By Its C-terminal Peptides Using mentioning
confidence: 99%
“…Although much smaller tetrapeptide inhibitors of LcA with nM k i have been described (30), the significance of the 32-mer peptide as an inhibitor lies in the fact that it is a part of the LcA itself, not resembling the true substrate. Recently, three hydroxamate-containing small molecule inhibitors having 5-6 M k i values were found to induce the most compact catalytic pocket in LcA (34).…”
Section: Inhibition Of Lca Activity By Its C-terminal Peptides Using mentioning
confidence: 99%
“…20 Silvaggi et al 21 determined the crystal structure of ortho-para-chloro-cinnamic hydroxamate revealing the hydroxamic acid chelates the active site zinc. Building on this finding, Thompson et al 22 an experimental K i of 1.29 μM using an HPLC-based assay and represents the first reported small molecule inhibitor identified that targets the BoNT/E catalytic site. 26 Recent follow up work by the same group, 27 employing pharmacophore modeling, led to the identification of four roughly equipotent analogs.…”
Section: Introductionmentioning
confidence: 98%
“…Hydroxamates have been shown to have efficacy in mice, but have relatively short in vivo half-lives [18]. Developing tight binding non-chelating inhibitors of BoNT/A has proven to be a difficult task in part due to the high conformational plasticity of the binding pocket and induced conformational changes in adjacent loops upon substrate or inhibitor binding [19]. The exceptionally large substrate binding surface of BoNT/A poses an extremely challenging problem to design effective small molecule inhibitors that are capable of disrupting the extensive protein-protein interactions within the substrate binding interface.…”
Section: Introductionmentioning
confidence: 99%